Assessment of biochemical and behavioral effects of carbaryl and methomyl in Brown-Norway rats from preweaning to senescence. (4th May 2015) - Moser, Virginia C.; Phillips, Pamela M.; McDaniel, Katherine L.
Highlights: Carbaryl and methomyl effects on motor activity and ChE inhibition in rats from PND18 to 24 mo. The only differences in ChE inhibition was seen in carbaryl-treated PND18 rats. Carbaryl and methomyl produced more motor activity depression and slower recovery at 12 and 24 mo. In vitro IC50s at different ages showed small differences with carbaryl but not methomyl. Abstract: Factors impacting life stage-specific sensitivity to chemicals include toxicokinetic and toxicodynamic changes. To evaluate age-related differences in the biochemical and behavioral impacts of two typical N -methyl carbamate pesticides, we systematically compared their dose–response and time-course in preweanling (postnatal day, PND, 18) and adult male Brown Norway rats ( n  = 9–10/dose or time) ranging from adolescence to senescence (1, 4, 12, 24 mo). Carbaryl was administered orally at 3, 7.5, 15, or 22.5 mg/kg and data were collected at 40 min after dosing, or else given at 3 or 15 mg/kg and data collected at 30, 60, 120, and 240 min. Methomyl was studied only in adult and senescent rat (4, 12, 24 mo) in terms of dose–response (0.25. 0.6, 1.25, 2.5 mg/kg) and time-course (1.25 mg/kg at 30, 60, 120, 240 min). Motor activity as well as brain and erythrocyte (RBC) cholinesterase (ChE) activity were measured in the same animals. In the carbaryl dose–response, PND18 rats were the most sensitive to the brain ChE-inhibiting effects of carbaryl, but 12- and 24-mo rats showed more motor activity depression even at similar levels of brain ChE inhibition. We have previously reported that brain ChE inhibition, but not motor activity effects, closely tracked carbaryl tissue levels. There were no age-related differences in methomyl-induced ChE inhibition across doses, but greater motor activity depression was again observed in the 12- and 24-mo rats. Carbaryl time-course data showed that motor activity depression reached a maximum later, and recovered slower, in the 12- and 24-mo rats compared to the younger ages; slowest recovery and maximal effects were seen in the 24-mo rats. Acetylcholinesterase sensitivity (concentration–inhibition curves) was measured in vitro using control tissues from each age. Inhibitory concentrations of carbaryl were somewhat lower in PND18, 12-, and 24-mo tissues compared to 1- and 4-mo, but there were no differences with methomyl-treated tissues. Thus, in the dose–response and time-course, there were dissociations between brain ChE inhibition and the magnitude as well as recovery of motor activity changes. The explanation for this dissociation is unclear, and is likely due to early development followed by aging-related decline in both kinetic parameters and neurological responsiveness.